Visuo-haptic virtual exploration of single cell morphology and mechanics based on AFM mapping in fast mode - Petit, C.; Kechiche, M.; Ivan, I. A.; Toscano, R.; Bolcato, V.; Planus, E.; Marchi, F. (Journal of micro-bio robotics, 2020)
Today the combination of several microscopy techniques over a sample can be performed at the same time on the same region. To fully capitalize on their complementarities and reveal new properties or behaviors as well as to present them in a new and attractive way, enhancing the experimental data exploration is a key issue. Especially, science education at micro and nanoscale is often limited by the complexity of making complicated knowledge accessible and easily remembered by the larger public. We propose an “out of the box” way to introduce complex scientific subjects like cell biology and polymer micro-rheology using haptic display and virtual reality. To reach this ambitious goal, firstly we combined the advantages of the Atomic Force Microscopy (AFM) and Fluorescence Microscopy (FM) in order to get complementary real experimental data on fixed and living isolated animal cells adhering on a protein micro-pattern or on a collagen-coated soft hydrogel. Secondly, thanks to the recent and fast AFM modes (PeakForce and Quantitative Imaging) dedicated to nanomechanical investigations, we achieved high resolution mapping images of the cell morphology, architecture and local mechanical properties. Then this set of data was implemented in a free simulation engine connected to a low-cost haptic device to create a virtual and interactive cell or polymer environment. In this environment, the user can explore the stiffness across three soft samples and can relate it to specific sample components. This dedicated visuo-haptic environment provides a novel sensory approach of the cell biology and/or micro(bio)mechanics through an active exploration of a set of scientific experimental data. This work paves the way to an affordable interactive and multisensory VR platform where various AFM images recorded in Peak Force or Quantitative Imaging, could be load in order to be actively explored; this approach fits into the emerging field of touching data.